2018
DOI: 10.3390/antiox7010021
|View full text |Cite
|
Sign up to set email alerts
|

The Addition of Manganese Porphyrins during Radiation Inhibits Prostate Cancer Growth and Simultaneously Protects Normal Prostate Tissue from Radiation Damage

Abstract: Radiation therapy is commonly used for prostate cancer treatment; however, normal tissues can be damaged from the reactive oxygen species (ROS) produced by radiation. In separate reports, we and others have shown that manganese porphyrins (MnPs), ROS scavengers, protect normal cells from radiation-induced damage but inhibit prostate cancer cell growth. However, there have been no studies demonstrating that MnPs protect normal tissues, while inhibiting tumor growth in the same model. LNCaP or PC3 cells were ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 48 publications
0
51
0
Order By: Relevance
“…Recently, an in vivo study conducted by Chatterjee el al. [40] showed that MnTE-2-PyP did not affect the metastatic progression of PC3 cells in an orthotopic prostate tumor model. On the other hand, in a mouse D-245MG glioma xenograft model, down-regulation of metastatic pathways was observed upon treatment with MnP + radiation vs radiation only [41] .…”
Section: Discussionmentioning
confidence: 95%
“…Recently, an in vivo study conducted by Chatterjee el al. [40] showed that MnTE-2-PyP did not affect the metastatic progression of PC3 cells in an orthotopic prostate tumor model. On the other hand, in a mouse D-245MG glioma xenograft model, down-regulation of metastatic pathways was observed upon treatment with MnP + radiation vs radiation only [41] .…”
Section: Discussionmentioning
confidence: 95%
“…This review is focused on understanding the spatiotemporal nature of MnSOD regulation in the context of a changing tumor microenvironment, which is necessary to improve the design of oxidant- or antioxidant-based therapeutic strategies for the treatment of cancer. In primary research articles by Chatterjee et al [ 8 ] and Heer et al [ 9 ], these investigators use SOD mimetics to enhance anti-cancer treatment. Chatterjee et al [ 8 ] demonstrate that SOD mimetics, in combination with radiation, inhibit prostate cancer growth while simultaneously protecting the normal prostate tissue from radiation damage.…”
mentioning
confidence: 99%
“…In primary research articles by Chatterjee et al [ 8 ] and Heer et al [ 9 ], these investigators use SOD mimetics to enhance anti-cancer treatment. Chatterjee et al [ 8 ] demonstrate that SOD mimetics, in combination with radiation, inhibit prostate cancer growth while simultaneously protecting the normal prostate tissue from radiation damage. Heer et al [ 9 ] enhance the anti-tumor effect of pharmacological ascorbate with the addition of SOD mimetics by enhancing hydrogen peroxide levels in the tumor.…”
mentioning
confidence: 99%
“…It has been previously shown that such MnPs protect from external beam radiation-induced salivary gland damage in head and neck cancer, but does not protect head and neck tumors from radiation-induced killing (Ashcraft et al 2015). Recent work has indicated that the MnPs act as a pro-oxidant in cancer cells by taking advantage of impaired antioxidant systems that allow accumulation of hydrogen peroxide to toxic levels, which results in the alteration of cell signaling and promotes cancer cell death (Kosmacek et al 2016;Tong et al 2016;Chatterjee et al 2018). The focus of the present study was to determine if MnTnBuOE-2-PyP could also be a highly effective and nontoxic radioprotective agent for therapeutic I-131 exposure.…”
Section: Discussionmentioning
confidence: 99%